(untitled) (Research, Society and Development, 2019)
Multilearning and multilevel social practices emerges in the 21st century as new pedagogical potentialities, but also challenges to teachers. Therefore, they need to be included in the debates and in the school discussions as a way of inserting them in the educational context. Thus, this article objetive to (re)know multiliterate practices developed by students of a peripheral community of Rio Grande do Sul as a way to subsidize the pedagogical practice of Geography and Portuguese Language. For this, a questionnaire, based on Rojo (2009) and Feltrin and Batista (2016), was applied to 74 studentes of primary school enrolled in the year 2018. It was observed that the students are included in the new media context of contemporaneity, presenting several multiliterate social practices that can subsidize the new pedagogical proposals and, consequently, stimulate new educational positions.